FAMILY SUPPORT FOR BREAST CANCER PATIENTS WHO ARE ANXIOUS ABOUT UNDERGOING CHEMOTHERAPY - Wahyudi, Rony; Trigantara, Regista; Fatmawati, Diana Noor (Poltekkes Kemenkes Malang, 2024)
The International Agency for Research on Cancer (IARC) 2018 stated that there is an increase in cancer sufferers every year and increase in cases of breast cancer affecting women with increasing death rates. Cancer will be the biggest obstacle for humans to increase life expectancy. The research method used observational analytic with a cross sectional approach. 40 respondents had breast cancer and underwent chemotherapy using a total sampling technique. The results showed that 37 respondents (92.5%) had high family support and 32 respondents (80%) had low anxiety. The results of the Spearman's rho test show a significance value of 0.000<0.05, it can be concluded that there is a relationship between family support and the level of anxiety in breast cancer patients undergoing chemotherapy at the oncology clinic at Dr. Saiful Anwar Malang, and correlation coefficient is -0,654, it’s means that the two variables have a strong correlation with a negative value. With good family support, anxiety resulting from separation can be overcome so that patients will feel comfortable while undergoing treatment. Patients who feel comfortable during treatment prevent a decrease in the immune system which affects the healing process. Adequate family support is expected to reduce patient anxiety, so that patients can focus on treatment and recovery.